Geometri Dalam Stuktur Bangunan Candi Borobudur Untuk Pembelajaran Berbasis Etnomatematika - Akmal Hi Dahlan; Almu Noor Romadoni (Peneliti.net, 2022)
This study aims to reveal the ethnomathematics contained in the Borobudur temple and the use of the Borobudur temple for ethnomathematics-based learning in schools. In this study, photos were used as learning media. This research is a qualitative descriptive research. The subjects in this study were divided into two, namely informants who knew information about Borobudur Temple and class VII students of SMP Pangudi Mulia Srumbung, Muntilan, Magelang, Central Java who would use the TSTS type learning model in learning. The object of this study is the Borobudur Temple and the simple mathematical elements contained in the temple. Borobudur Temple and Schools near Borobudur Temple who know, understand, and are close to the daily life of the temple and the culture at Borobudur Temple were selected as research data sources. The results of the study show that ethnomathematics is good for learning in schools that are close to students' real lives. The results showed that after applying ethnomathematics-based learning using the TSTS type learning model it could increase students' activeness and confidence in expressing opinions. Suggestions, as teaching staff should create an innovation that can develop talent, foster interest and improve students' learning habits, so that the concept of learning mathematics obtained is expected to be better and considered cultural issues so that mathematics is not too far from students' real life